Sharia Audit in Indonesia: Implementation, Challenges, And Future Prospects: Audit Syariah di Indonesia: Implementasi, Tantangan, dan Prospek Masa Depan - Fadhlihi, Andueriganta; Yufantria, Fenni; Etika, Citra (Perisai : Islamic Banking and Finance Journal, 2025)
This study aims to examine how the implementation of Sharia audit is carried out in Indonesia and to identify the challenges that must be addressed for future development. This research employs a qualitative approach using a literature review method. The findings of this study indicate several issues in the development of Sharia audit in Indonesia, including weak regulations related to Sharia auditing, limited numbers and competencies of Sharia auditors, and the absence of a comprehensive Sharia audit standard. These findings highlight the need to strengthen the regulatory framework, enhance auditor competencies, and establish national Sharia audit standardization to reinforce governance, accountability, and public trust in Indonesia’s Islamic financial institutions.